SMANTI Education Festival (SEF) Basis for Instilling Tolerance Values - Faridi (LETIGES, 2024)
This study aimed to determine the implementation and implications of instilling tolerance values through SMANTI Education Festival (SEF). SMANTI is an acronym for SMA Negeri 3 Malang. This study needs to be conducted to prove that educational institutions are the most appropriate choice for instilling tolerance values. This means that academic institutions can be a laboratory for instilling religious tolerance values so that students can behave and act moderately, understand religious teachings correctly, and interact well in a pluralistic society. The research method uses a Qualitative Approach with a case study research type and data collection techniques through interviews, observations, and documentation. The data analysis technique uses a descriptive-exploratory model involving three components: data reduction analysis, data presentation, and conclusion drawing. The findings in this study are the instillation of tolerance values in SMAN 3 Malang, among others, through the SMANTI Education Festival (SEF) which is implemented in seven types of competitions, as follows: SMANTI Olympiad Competition, Bhawikrsu Islamic Fair, SMANTI Language and Literature Festival, IT-Festival, PBB Competition and Formation Competition, Bhawikrsu Red Cross Youth Competition Fair, Bhawikarsu English Vaganza. Held annually in East Java, involving students at elementary/MI, junior high/MTs and senior high/MA levels and equivalent. The implication of this study is to equip students with ways to overcome problems and solve problems appropriately, quickly, and accurately to achieve success and success in the future. Students not only learn how to compete well but also learn individual responsibility and teamwork to achieve the expected results and practice fair play values consistently.